(untitled) (Revista Brasileira de Ciências do Envelhecimento Humano, 2013)
Changes in cognitive and motor ability performance due to advancing age can compromise daily activities. It is important to determine if the maze test can be sensitive to the cognitive or motor alterations of normal ageing. This, the aim of the study was to verify age-related differences in executive function, learning and short-time memory by means of the maze test. Participated 80 healthy individuals, 40 young people (22 ± 2 years) and 40 elderly individuals (67 ± 5 years), underwent a health and cognitive evaluation (Mini Mental State Examination). Participants were timed solving thirty mazes, and another 15 minutes later. The data were analyzed by ANOVA and multiple linear regression. The elderly subjects took longer to solve the mazes, suggesting difficulties in executive function; learning took place in the first trials and a short-time memory deficit occurred. A correlation was observed between the cognitive and maze test (r = -0.320; p = 0.003). Age was the only predictive factor of performance. It is suggested that the maze test may contribute to the monitoring of premature cognitive and motor alterations in the elderly.